Simulation of red tide drift-diffusion process in the Pearl River Estuary and its response to the environment - Xu, Yuanxing; Sun, Yan; Xu, Guangjun; Liu, Dazhao (Frontiers in Marine Science, 2023)
A particle tracking model for the Lingdingyang Bay of the Pearl River Estuary (PRE) was established based on the Delft3D model. The model was initialized with remote sensing images to simulate the red tide drift-diffusion process in this sea area in the autumn of 2020 and analyze its response to tides, winds and runoffs. The results show that this red tide occurred in the central sea area of the Lingdingyang Bay. The red tide drifted south with the ebb tide and north with flood tide. The red tide spread northward to the waters near Humen and southward to the western waters of Zhuhai. Through the control variable experiments, it is found that the red tide drift-diffusion process was mainly affected by tide and wind, with minimal influence from runoff. The tide expanded the scope of red tide diffusion, and the wind further changed the distribution of red tide. Under the influence of the northeast wind, the red tide gathered on both sides of Lingdingyang Bay. Comparison with the red tide drift-diffusion process in the sea area near Shenzhen Airport shows that the red tide near Neilingding Island easily diffused toward surrounding waters.